Uji Kinerja Portable Rainfall Simulator pada Berbagai Tekanan untuk Mengukur Keseragaman dan Intensitas Hujan - Ridwan, Ridwan; Oktafri, Oktafri; Amin, Muhammad; Berdikari, Rendi Amanda (Jurnal Agricultural Biosystem Engineering, 2022)
Indonesia is located in a tropical climate, which only has rainy and dry seasons. However, the seasonal pattern in Indonesia can no longer be used as a reference, especially the rainy season. This causes environmental problems, one of which is erosion. To overcome these problems, it can be done by simulating artificial rain using a portable rainfall simulator. This study aims to determine the performance test of a portable rainfall simulator at various pressures to measure the uniformity and intensity of rain. This research was conducted by testing the Portable Rainfall Simulator with various pumping pressures, namely 1.5, 1.8, and 2.1 bar with a test time of 15, 30, 45, 60, and 75 minutes, respectively. The results showed that the Portable Rainfall Simulator produced rain discharge with a uniformity level (CU) greater than 70%. This means that the artificial rainwater produced by the Portable Rainfall Simulator nozzle has a good level of uniformity and has good performance. Portable Rainfall Simulator with adjustable nozzle is only able to produce rain intensity criteria at various pressures, namely very light rain and light rain at pressures of 1.5, 1.8, and 2.1 bar. In addition, the pumping pressure affects the value of the uniformity coefficient of the radiated discharge (CU), the greater the operating pumping pressure, the greater the value of the uniformity coefficient of the radiated discharge (CU). However, this pumping pressure has no effect on the value of rain intensity. Keywords:  Climate, Erosion, Portable Rainfall Simulator, Rain.